Assessing Postpartum Depression and Anxiety during the Antenatal and Postpartum Period : Postpartum Depression and Anxiety - Ratyal, Sania; Saeed, Shazia; Hameed, Nasreen; Sabir, Farzana; Akram, Sara; Habib, Maniba (Pakistan Journal of Health Sciences, 2024)
Postpartum Depression (PPD) and anxiety were common mental disorders affecting women during the antenatal and postpartum periods. Early detection and intervention were vital for improving maternal and infant health outcomes. Objective: To assess the postpartum depression and anxiety during the antenatal and postpartum period using postnatal depression scale (EPDS) and the hospital anxiety and depression scale (HADS). Methods: Total 94 patients over six months in the Department of Obstetrics and Gynecology at Divisional Headquarters Teaching Hospital in Mirpur, Azad Kashmir were enrolled in this comparative cross sectional study. The pregnant women aged 18 to 45 during third trimester were included and excluding those with pre-existing psychiatric conditions or high-risk. The study utilized the HADS and EPDS while also recording demographic and clinical information, including age, education level, socioeconomic status, marital status, parity, gestational age at delivery, gestational diabetes, and preeclampsia. Data were analyzed using SPSS version 26 with appropriate statistical methods. Results: The majority of participants were over 25 years old (71.3%) and undergraduate education (62.8%), with 67.0% being multiparous. Gestational diabetes was present in 19.1%, and 16.0% had hypertension. HADS identified 15 mild, 35 moderate, and 44 severe cases, while EPDS reported 19 mild, 30 moderate, and 45 severe cases, with both scales showing the highest prevalence in the severe category. Conclusions: EPDS and HADS were two good screening tools for postpartum depression as well as anxiety. Using both together can certainly enhance the detection procedure, leading to timely intervention and a better prognosis of maternal as well as infant health.